Immune Activation and Neuroinflammation in Alcohol Use and HIV Infection: Evidence for Shared Mechanisms - Monnig, Mollie A. (Am J Drug Alcohol Abuse, 2016)
BACKGROUND: Emerging research points to innate immune mechanisms in the neuropathological and behavioral consequences of heavy alcohol use. Alcohol use is common among people living with HIV infection (PLWH), a chronic condition that carries its own set of long-term effects on brain and behavior. Notably, neurobiological and cognitive profiles associated with heavy alcohol use and HIV infection share several prominent features. This observation raises questions about interacting biological mechanisms as well as compounded impairment when HIV infection and heavy drinking co-occur. OBJECTIVE AND METHOD: This narrative overview discusses peer-reviewed research on specific immune mechanisms of alcohol that exhibit apparent potential to compound the neurobiological and psychiatric sequelae of HIV infection. These include microbial translocation, systemic immune activation, blood-brain barrier compromise, microglial activation, and neuroinflammation. RESULTS: Clinical and preclinical evidence supports overlapping mechanistic actions of HIV and alcohol use on peripheral and neural immune systems. In preclinical studies, innate immune signaling mediates many of the detrimental neurocognitive and behavioral effects of alcohol use. Neuropsychopharmacological research suggests potential for a feed-forward cycle in which heavy drinking induces innate immune signaling, which in turn stimulates subsequent alcohol use behavior. CONCLUSION: Alcohol-induced immune activation and neuroinflammation are a serious health concern for PLWH. Future research to investigate specific immune effects of alcohol in the context of HIV infection has potential to identify novel targets for therapeutic intervention.